Corrosion Inhibition Performance of Euphorbia pulcherrima Bark Extract in 1M H2SO4 on Mild Steel - Gupta, Dipak Kumar; Gurung, Shilpa; Karki, Nabin; Yadav, Amar Prasad (NUTA Journal, 2023)
The bark of the attractive flower Euphorbia pulcherrima (Lalupate), which is widely accessible in Nepal, can be used to extract an alkaloid that acts as a corrosion inhibitor. The methanolic extract of Euphorbia pulcherrima (EP) in 1M H2SO4 was employed to study corrosion inhibition of mild steel (MS) by weight loss and potentiodynamic technique. The immersion time and EP extract concentration consequences on corrosion inhibition were explored. The weight loss of MS is significantly reduced in the presence of EP inhibitors caused by the adsorption of inhibitor molecules. The findings exhibited that the increasing immersion time and EP concentration resulted in an increment in inhibition efficiency (IE). The maximal IE from the weight loss method was determined to be 90.38% for 1000 ppm extract immersed for 6 hours at room temperature and 86.36% IE was obtained for 1000 ppm concentration of the EP extract after 1hr of immersion by potentiodynamic polarization. The open circuit potential (OCP) of the MS in the inhibitor solution confirmed the EP extract behaving as a mixed inhibitor. The current density decreased with the addition of the EP, which reflected the inhibitive nature of inhibitor molecules. Similarly, the corrosion current density decreased as the EP extract concentration increased. Hence, it implied that the bark extract of EP is a potent inhibitor of MS corrosion, even after just one hour of immersion. Because of the reduction of hydrogen ions and the adsorption of inhibitor molecules on the MS surface, EP extract is effective in inhibiting corrosion current on the cathodic and anodic polarization curves, forming a barrier that stops the evolution of hydrogen gas and metal dissolution. Fourier Transform Infrared (FTIR) spectroscopic analysis showed the presence of N-H and C=O functional groups in the EP attributed to the adsorption on MS and consequently reducing the dissolution of MS.